Marangoni Driven Boundary Layer Flow of Carbon Nanotubes Toward a Riga Plate - Shafiq, Anum; Zari, Islam; Khan, Ilyas; Khan, Tahir Saeed; Seikh, Asiful H.; Sherif, El-Sayed M. (Frontiers in Physics, 2020)
The objective of this article is to explore radiative Marangoni boundary layer flow of carbon nanotubes along a surface that is an electromagnetic actuator, such as a Riga surface. A comparative study is conducted to investigate the behavior of Lorentz forces on the basis of nanoparticle temperature fluxes with two different types of carbon nanotubes, namely single-wall carbon nanotube and multi-wall carbon nanotubes saturated into water as the base fluid. The proposed schemes of governing equations are then converted into ordinary differential equations by similarity transformation. One of best analytical methods, the homotopy analytical method, is utilized for the solution of the governing equations and the convergence of the control parameters. Embedded dimensionless parameters of the flow fields are examined via graphical illustrations. It is observed that an increase in the modified Hartmann number increases the velocity field but reduces the temperature distribution.